PENGARUH SENAM DISMENOREA TERHADAP PENGURANGAN RASA NYERI SAAT MENSTRUASI - Maita, Liva (Sistem Informasi, 2016)
Gymnastics Dysmenorrhea is a relaxation technique that is used to reduce pain during menstruation . This study aims to look at the effect of exercise disminore to reducing pain during menstruation in Prodi DIII Midwifery student STIKes Hang Tuah Pekanbaru 2015. Quasi research type experiment with pretest and posttest study design . Samples taken as many as 30 students who experience dysmenorrhea Data analysis Univariate and Bivariate with Dependent T test . Results of research on the influence of gymnastics disminore get to the reduction of pain during menstruation , with p value 0,000 Value ( p < 0.05 ) . Disaranaka to the student to be able to learn and practice gymnastics dysmenorrhea every month before menstruation and after menstruation .